2015
DOI: 10.1159/000431376
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Tinnitus in the Italian Adult Population

Abstract: Background: Limited, outdated, and poor quality data are available on the prevalence of tinnitus, particularly in Italy. Methods: A face-to-face survey was conducted in 2014 on 2,952 individuals, who represented the Italian population aged 18 or more (50.6 million). Any tinnitus was defined as the presence of ringing or buzzing in the ears lasting for at least 5 min in the previous 12 months. Results: Any tinnitus was reported by 6.2% of Italian adults, chronic tinnitus (i.e. for more than 3 months) by 4.8%, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 45 publications
6
75
1
Order By: Relevance
“…Gender was predominately male in all three samples and this result is in line with previous research on tinnitus: “In fact, most previous studies, but not all … showed higher tinnitus prevalence in men than in women” (Gallus et al, 2015; p. 16). The crowdsourcing platform Tinnitus Talk had the highest percentage of female individuals, whereas the crowdsensing platform TrackYourTinnitus had the lowest.…”
Section: Discussionsupporting
confidence: 91%
“…Gender was predominately male in all three samples and this result is in line with previous research on tinnitus: “In fact, most previous studies, but not all … showed higher tinnitus prevalence in men than in women” (Gallus et al, 2015; p. 16). The crowdsourcing platform Tinnitus Talk had the highest percentage of female individuals, whereas the crowdsensing platform TrackYourTinnitus had the lowest.…”
Section: Discussionsupporting
confidence: 91%
“…More than one billion dollars was disbursed in disability payments by the United States Government in 2011 to members of the military suffering from tinnitus. Of the general population approximately 1–2% of individuals suffer from unremitting tinnitus to the extent that they seek assistance from the health professions including family physicians, otolaryngologists, audiologists, psychiatrists, and neurologists [1, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…While a large percentage of cases is only minimally impaired during their daily routing, the severe cases of tinnitus are affected by anxiety, depression, insomnia and concentration problems all of which can impair their quality of life (Dobie, 2003; Heller, 2003; Kreuzer et al, 2013). Epidemiological studies of tinnitus indicate a prevalence between 6%–26% with 1.2%–1.6% reporting severely annoying tinnitus (Davis and Rafaie, 2000; Hasson et al, 2010; Gallus et al, 2015). There is currently little evidence for an effective treatment of tinnitus loudness and no pharmacological treatment approved by the US Food and Drug Administration (FDA) or the European Medicines Evaluation Agency (EMEA; Langguth and Elgoyhen, 2012).…”
Section: Introductionmentioning
confidence: 99%